Comparative Analysis Of Performance Of Teacher Recipients And Non-Recipients Of Incentives In The LPQ Coordination Environment Agency, Kedu Sub-District, Temanggung District - Fahrub, Abdul Wahab; Shifah, Akhida Layinatush (AL-WIJDÃN Journal of Islamic Education Studies, 2024)
Teachers are an important element in implementing educational programs through learning activities in formal and nonformal education. Giving an incentive of IDR 100,000 per month is a form of government attention to teachers in the hope of improving their performance. The government distributes this incentive in collaboration with the Ministry of Religion at the regency level. With this nominal, the teachers remain enthusiastic and teach; even teachers do not receive incentives but remain enthusiastic in teaching students every day. The purpose of this study was to determine the performance of the teachers and the significance of differences in the performance of incentive recipients and non-incentive recipients within the Coordinating for Qur'an Education Institutions of the Kedu subdistrict. The research approach uses mixed method research (MMR), namely research that combines qualitative and quantitative forms with data collection techniques through questionnaires, interviews, documentation, and observation. The research population is the teachers in the Coordinating for Qur'an Education Institutions of Kedu subdistrict with a sample of 30 people. The performance of the teachers in the Coordinating for Qur'an Education Institutions of Kedu subdistrict is generally good based on seven aspects of assessment: teaching preparation, being fair (non-discriminatory), giving awards to students, applying discipline to students, applying appropriate learning, recognizing students in situations, and have exemplary actions. Good performance is influenced by several factors, namely ability, motivation, and individual, and environmental factors. Evidenced by the results of the analysis using the independent sample t-test with the value of count on the assumed equal variances obtained a value of 0.271 and for the sig p-value of 0.353 > 0.05 so it can be concluded that there is no significant difference between the performance of incentive recipient and non-recipient teachers.   Keywords: Teacher Performance, Incentives, Qur'an Educational Institutions